Differentiate y=x^3*(x^2+1)

As this is a product of two functions it is necessary to use the product rule for differentiation. Therefore one of the functions must labeled v and the other u. i.e. u=x^3 and v=(x^2+1). It is then necessary to differentiate each of those functions seperately so that du/dx=3x^2 and dv/dx=2x. The final step is to multiply v by du/dx and multiply v by du/dx then add the two together as follows: dy/dx=2x^4+3x^2*(x^2+1)

Answered by Bevan J. Maths tutor

3080 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Integrate Cos^2(x)


Express 4sinx-cos(pi/2 - x) as a single trignometric function


Find the equation of the tangent to the curve y = (2x -3)^3 at the point (1, - 1), giving your answer in the form y = mx + c.


integrate [xe^(-x)] with respect to x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences